Maintaining efficiency while integrating entrants from lower-performing environments: An experimental study - Timothy C. Salmon; Roberto A. Weber (University of Zurich, Department of Economics, 2011)
Efficient growth often requires the integration of individuals from lower-performing groups, firms, or societies into higher-performing ones. Such integration may be difficult without facilitating interventions or restrictions. We explore, using a laboratory experiment, the effectiveness of two regularly-employed entry restrictions: entry quotas and entry exams. We use a coordination game with Pareto-ranked equilibria, in which we allow an effciently-coordinated group and an ineffciently-coordinated one to arise endogenously. We then allow individuals to move from the low-performing group to the high-performing one. We vary whether such movement is unrestricted, is limited to one entrant per period, or is subject to passing an entry exam. We find both kinds of restrictions improve the efficient integration of entrants, but that there is no additional benefit obtained by their combination. The restrictions lead to improved behavior among entrants, but they have a stronger influence on the maintenance of good behavior among incumbents in the high-performing group.
Keywords: C72; C92; M12; 330; Growth; Entry; Coordination; Experiments; Gruppenentscheidung; Mitgliedschaft; Soziales Verhalten; Nichtkooperatives Spiel; Test